Cycling Under Influence: Summarizing the influence of attitudes, habits, social environments and perceptions on cycling for transportation. (Paper accepted for presentation at the 92nd Transportation Research Board Annual Meeting, Washington D.C., USA) - Willis, Devon Paige; Manaugh, Kevin; El-Geneidy, Ahmed M. (My University, 2013)
Due to cycling s many benefits, research on factors that could increase this activity has greatly expanded. Clear connections have been found between elements of the built environment and cycling for transportation. However, social and psychological factors, such as attitudes, perceptions, and habits, have recently been shown to play an important role in affecting travel behaviour and mode choice. This review paper sets out to summarize the literature concerning the influence of these social and psychological factors on the choice to cycle for transportation. The findings highlight the importance of these factors on bicycle commuting; implications for policy are presented. (D.P.W. et al.)
Keywords: Individualverkehr; Fahrradverkehr; Mobilität; Verkehrsmittelwahl; Gewohnheit; Fahrradnutzung; Bedürfnis; Emotion; Einflussfaktor; Verkehrspsychologie; Radverkehrsförderung